(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
The selection of appropriate rattan for a certain use must be based on adequate information about its potency, anatomical structure, and chemical properties. Standards methods of inventory development by Curtis method was used to obtain data on its density and frequency. To know the anatomical structure of preparation were made according to Schultze method and microtome preparation according to Staining Paraffin Section with Safranin. While to know the chemical component of rattan stem the analyzed by Standard Industry Indonesia procedures. Calamus occidentalis is one among other Java rattan species which its distribution is limited in the area of Ujung Kulon National Park, West Java. C. occidentalis may be utilized for various purposes based on the following characteristics: species density of 21 cane/ha; and anatomical structure: fiber length of 2204 Î¼m, fiber-wall thickness of 4.26 Î¼m, vascular bundle diameter of 812.5 Î¼m, metaxylem diameter of 293.75 Î¼m, proxylem diameter of 43.5 Î¼m, and phloem diameter of 37.5 Î¼m. Its chemical components are cellulose (49.95%), lignin (22.39%), and air-dry moisture (12.27%). Based on the above information, C. occidentalis rattan species possibly can be used as an alternative substitute of Calamus manan, an endangered rattan species, because several properties of C. occidentalis has similar with that of C. manan. Â© 2004 Jurusan Biologi FMIPA UNS Surakarta Keywords: commercial-value, possible utilization, Calamus occidentalis